Hybrid sandwich panels: A review - Srinivasa, Venkateshappa Chikkol; Sandeep, S.H. (Zielona Góra: Uniwersytet Zielonogórski)
A high specific stiffness, high specific strength, and tailoring the properties for specific application have attracted the attention of the researchers to work in the field of laminated composites and Sandwich structures. Rapid use of these laminated composites and Sandwich structures necessitated the development of new theories that suitable for the bending, buckling and vibration analysis.
Keywords: beams; shells; Fibre Metal Laminate (FML); free vibrations; natural frequency; sandwich plates; sandwich cylindrical shells; beam theories; higher-order theory; shear deformation theory